Analiza nawyków i zachowań związanych ze stosowaniem środków przeciwbólowych dostępnych bez recepty = Analysis of habits and behaviours related to the use of over-the-counter painkillers - Kozłowski, Piotr; Cuch, Barbara; Kozłowska, Magdalena; Kozłowska, Karolina; Jędrzejewska, Barbara (Journal of Education, Health and Sport, 2015)
Kozłowski Piotr, Cuch Barbara, Kozłowska Magdalena, Kozłowska Karolina, Jędrzejewska Barbara. Analiza nawyków i zachowań związanych ze stosowaniem środków przeciwbólowych dostępnych bez recepty = Analysis of habits and behaviours related to the use of over-the-counter painkillers. Journal of Education, Health and Sport. 2015;5(3):174-182. ISSN 2391-8306. DOI: 10.5281/zenodo.16307 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A174-182 https://pbn.nauka.gov.pl/works/549409 http://dx.doi.org/10.5281/zenodo.16307 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 12.03.2015. ANALIZA NAWYKÓW I ZACHOWAŃ ZWIĄZANYCH ZE STOSOWANIEM ŚRODKÓW PRZECIWBÓLOWYCH DOSTĘPNYCH BEZ RECEPTY. Analysis of habits and behaviours related to the use of over-the-counter painkillers. Piotr Kozłowski1, Barbara Cuch1, Magdalena Kozłowska2, Karolina Kozłowska3, Barbara Jędrzejewska4 1 Katedra i Zakład Anatomii Prawidłowej Człowieka, UM w Lublinie 2 Katedra i Zakład Farmakologii doświadczalnej i Klinicznej, UM w Lublinie 3 Instytut Filologii Angielskiej, KUL 4 Państwowa Szkoła Wyższa im. Papieża Jana Pawła II w Białej Podlaskiej Uniwersytet Medyczny w Lublinie ul. W. Chodźki 1, 20-093 Lublin e-mail: piotr7176@gmail.com Abstrakt Celem pracy była ocena nawyków i zachowań związanych ze stosowaniem środków przeciwbólowych. Badaniem objęto 108 osób. W grupie badanej kobiety stanowiły 67,6% ankietowanych, natomiast mężczyźni 32,4%. Wiek ankietowanych zawierał się w przedziale od 20 do 60 lat. Badanie przeprowadzono w okresie od stycznia do lutego 2015 roku metodą wywiadu standaryzowanego. Narzędziem badawczym, którym posłużono się do zebrania danych, był autorski kwestionariusz. Kwestionariusz zawierał 29 pytań z możliwością jednokrotnego wyboru. Przeprowadzono analizę statystyczną z wykorzystaniem testu chi-kwadrat. Wszystkie wartości w których p<0,05 uznano za istotne statystycznie. Prawie połowa ankietowanych (46,3%) odpowiedziało, że zażywa leki przeciwbólowe sporadycznie. Częste użycie (raz lub kilka razy w tygodniu) leków analgetycznych deklarowało 12,9% ankietowanych. Najczęstszym powodem stosowania analgetyków przez kobiety były bóle menstruacyjne aż 52,1% pań wybrało tę odpowiedź. Mężczyźni najczęściej sięgali po leki przeciwbólowe z powodu bólu głowy (48,6% ankietowanych mężczyzn). Najczęściej wybieraną substancją przeciwbólową był ibuprofen (34,3% ankietowanych stosowało tę substancję). Na pytanie: „Kto polecił Panu/Pani, który lek przeciwbólowy wybrać?”, 49,1% ankietowanych odpowiedziało, że sami zdecydowali o wyborze leku przeciwbólowego, tylko 16,7% skorzystało z porady lekarza, a 0,9% zasugerowało się reklamą. Ponad jednej trzeciej respondentów (38,9%) zdarzyło się przyjmować leki przeciwbólowe razem z alkoholem. Nie było tu istotnej różnicy biorąc pod uwagę płeć. Słowa kluczowe: środki przeciwbólowe, analgetyki. Abstract The aim of the study was to evaluate the habits and behaviours associated with the use of painkillers. The study included 108 participants. In the study group, 67.6% of respondents were females whereas 32.4% were males. The age of participants ranged from 20 to 60 years. The study was conducted in the period from January to February 2015 and it employed standardized interview research method. Research tool, which was used for data collection was a questionnaire consisted of 29 questions multiple-choice questions. Statistical analysis was performed using the chi-square test. All values for which p <0.05 (probability of error) were considered statistically significant. Almost half of the respondents (46.3%) stated that they took painkillers occasionally. Frequent use (once or several times a week) of analgesic medication was declared by 12.9% of respondents. In females, the most common reason for the use of analgesics were menstrual cramps (52.1% of female participants). In males, the main reason were headaches (48.6% of male respondents). The most commonly used painkiller was ibuprofen (34.3% of the respondents). To the question "who advised you to choose a particular painkiller?" 49.1% of the respondents answered that they had made the decision themselves, only 16.7% had received advice from their doctor, whereas 0.9% admitted to having been influenced by advertising. More than one-third of the respondents (38.9%) admitted to having taken painkillers with alcohol, in which case the results were similar for both sexes. Key words: painkiller, analgesic.